Pengembangan LKPD Berbasis Guided Inquiry Learning untuk Siswa Kelas V di SD Negeri 61 Lubuklinggau - Saputra, Tri Maulana; Krisnawati, Yuni; Sofiarini, Andriana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to develop teaching materials in the form of LKPD based on Guided Inquiry Learning for fifth grade elementary school students that are valid and practical. This type of research is research and development (Research and Development) with the ADDIE development model. Data collection techniques through interviews, observation, questionnaires, tests and documentation with research subjects, namely fifth grade students at SD Negeri 61 Lubuklinggau. Based on the results of the validation test analysis of the Guided Inquiry Learning-based LKPD which was assessed by three experts, namely, language experts, media experts and material experts, they met the validity criteria with an average score of 0.84. Meanwhile, from the results of the analysis of teacher and student practicality sheet assessments, it was found that the Guided Inquiry Learning-based LKPD met the practical criteria with an average score of 90.43%. Based on the research results, it can be concluded that the Guided Inquiry Learning-based LKPD has been proven to be valid and practical, making it suitable for use. Keywords: Guided Inquiry Learning, LKPD, Development, Elementary School.